Adolescents’ Perceptions of Marriage Age Maturity through the Generation Planning Program in Sanetan Village, Rembang Regency - Praseptya, Rizky Hengki; Kisworo, Bagus (Jurnal Aspirasi, 2025)
Early marriage remained a significant issue in Indonesia due to its impact on adolescents’ reproductive health, education, and future. However, there was a research gap, as few studies examined adolescents’ perceptions of delayed marriage age (PUP) within local contexts, such as in Sanetan Village, Sluke District, Rembang Regency. This study addressed that gap by exploring the experiences and perspectives of adolescents, both those involved in the Youth Information and Counseling Center (PIK-R) and those who were not, within the framework of the Generasi Berencana (GenRe) Program. This study used a qualitative approach to investigate adolescents’ views, attitudes, and experiences through in-depth interviews and observations with adolescents, Youth Family Development (BKR) cadres, and Family Planning Field Officers (PLKB). The findings indicated that adolescents who participated in PIK-R demonstrated better understanding of the risks of early marriage and the importance of physical and mental readiness before entering marriage. In contrast, adolescents not engaged in PIK-R tended to have limited perceptions, which were strongly influenced by cultural norms and social pressures. These findings underscore the importance of expanding access to and participation in PIK-R programs to enhance adolescents’ knowledge and awareness of PUP. Based on these results, recommendations were directed to the House of Representatives of the Republic of Indonesia, particularly Commission IX, to encourage the government on to strengthen the GenRe Program through a more comprehensive, community-based approach. Locally informed and data-driven policies are essential to promote PUP and to reinforce adolescent reproductive health education in Indonesia.